Pengaruh Supervisi Akademik Pengawas Sekolah Kepemimpinan Kepala Sekolah Terhadap Kepuasan Kerja Guru Pada SMA/SMK di Kecamatan Pulau-Pulau Terselatan Kabupaten Maluku Barat Daya Provinsi Maluku - Vemy Laimeheriwa (Jurnal Evaluasi Pendidikan, 2022)
Abstract: The study aims at discovering (1) the description of teachers' working satisfaction, academic supervision of schools' supervisors, the principals' leadership in Pp. Terselatan subdistrict (the southern farthest islands subdistrict) and (2) the influence of academic supervision of schools' supervisors, the principals' leadership on working satisfaction of high school teachers in Pp Terselatan subdistrict. The research method consisted of (1) the type of ex-post-facto research, (2) the research population was the entire civil servant teachers included part-time teachers of SMA/SMK in Pp. Terselatan subdistrict with a total of 109 teachers, (3) the samples were 90 people which meant above the minimum sample limit based on Slovin formula, (4) the research variables consisted of one independent variable, mely academic supervision of schools' supervisors (X1), one variable of intervening the principals' leadership (X2), and one dependent variable, namely teachers' working satisfaction (Y), (5) data collection was in a form of a questionnaire, and (6) data analysis technique used descriptive analysis and inferential analysis techniques. The results showed that (1) School Supervisor Academic Supervision with a variance of 418.14 was in the fairly good category, Principal Leadership with a variance of 331.96 was in the fairly good category, and Teacher Job Satisfaction with a variance of 165.97 was in a good category; (2) there is a direct influence of School Supervisor Academic Supervision which is significant towards Principal Leadership at 12.53% with path coefficients of ⍴ = 354 > α = 0.05; (3) there is no direct influence of School Supervisory Academic Supervision on Teacher Job Satisfaction with a path coefficient of ρ = -0.158 < α = 0.05; (4) there is a direct effect of significant Principal Leadership on Teacher Job Satisfaction of 32.83% with path coefficients of ⍴ = 0.573 > α = 0.05, and (5) there is an indirect influence of School Supervisors Academic Supervision on Teacher Job Satisfaction through Principal Leadership amounting to 20.28%.